Market Exposure and the Labour Process: The Contradictory Dynamics in Managing Subcontracted Services Work. (February 2019) - Grimshaw, Damian; Cartwright, Jo; Keizer, Arjan; Rubery, Jill
Marketization of the employment relationship is a key causal factor explaining the adverse impact of subcontracting low-wage services on employment conditions. This article extends existing sociological theory by analysing the market-making and rule-breaking roles of client and subcontractor firms through qualitative data. It finds that client organizations construct different types and temporalities of marketized cost pressures, that clients and subcontractors exploit their power advantage over labour to evade institutional rules and that labour process and reputational concerns impose a degree of moderation towards socially desirable outcomes. The theoretical framework 'unpacks' marketization by distinguishing the interplay between contracts, regulation and labour process requirements as shaped by clients and subcontractors. In the UK cleaning sector, the potentially positive effects of client and subcontractor actions on employment conditions are marginal, focused on non-pay aspects and introduced primarily for reputational reasons. The evidence indicates the limits of voluntary action and the need for regulation.